Analisis kelayakan bisnis: Warung makan Mbak Anni di Kota Batu dalam menghadapi tantangan industri kuliner - Zahro, Tazkiya Shofiyatuz; Rofiah, Aminatur; Sufia, Ilma; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2024)
Warung Makan Mbak Anni is one of the culinary places in the center of Batu City. This stall was founded in 2002. The aim of this research is The aim of this research is to analyze legal aspects, environmental aspects, market and marketing aspects, technical and technological aspects, management and human resources aspects, financial aspects and AMDAL aspects of Mbak Anni's Warung in Batu City in facing the challenges of the culinary industry. This research method is a qualitative method used to analyze legal, marketing, technical and technological, management and organizational, financial and AMDAL aspects, in the feasibility study of Mbak Anni's food stall business in Batu City. This method can be carried out using interviews, observation, or content analysis. The results of this research are Based on the feasibility analysis of Warung Mbak Anni, the conclusion is that this business is generally considered feasible with fairly good feasibility scores in various aspects, including legal, environmental, market and marketing, engineering and technology, management and human resources, financial, as well as AMDAL aspects. However, there are several recommendations that can be implemented to improve business performance and sustainability.